Occupational Therapists’ Understanding of Autonomy for People with Dementia - (OTNZ, M.OT), Carlie Foster; (PhD, OTNZ), Dr. Mary Butler (International Journal of Innovative Research in Medical Science, 2017)
The purpose of this qualitative descriptive study was to investigate the views of occupational therapists at one of New Zealand’s largest District Health Boards (DHBs) regarding their understanding of autonomy for people with dementia in relation to placement decision making. Using purposive sampling, six participants were individually interviewed using a semi-structured interview template. Interviews were digitally recorded, transcribed verbatim, and thematically analysed. The results of the study indicate that despite therapists having a theoretical understanding of autonomy, there are significant barriers to effective practical implementation for people with dementia. People with dementia are often cared for by an occupational therapy workforce which is inexperienced in dementia care (in a general health setting), with capacity status used reactively by the multi-disciplinary team and largely in situations where a decision is being forced upon a person with dementia. Access to the required skilled government funded caregiving support is lacking and proves a major determinant of placement along with other factors including perceived risk to the person by the placing therapist. Patient choice seemingly plays little role in the placement decision-making process.